Bioactive Properties of Hazelnut-Derived Products in Colorectal Cancer Prevention: A Systematic Review of Preclinical and Epidemiological Studies - Giuseppe Mazzola; Mariangela Rondanelli; Federico Buga; Patrizia Riso; Simone Perna (Foods, 2025)
Background: Colorectal cancer (CRC) is among the leading causes of cancer-related mortality worldwide, with increasing attention being paid to modifiable dietary factors in its prevention. Hazelnut (Corylus avellana L.) represent a nutrient-dense food rich in unsaturated fats, polyphenols, fiber, and phytosterols, with potential anticarcinogenic properties. This systematic review aimed to evaluate the role of hazelnut consumption in the prevention and modulation of CRC risk, with specific focus on experimental, mechanistic, and preclinical evidence. Methods: Following PRISMA guidelines, a systematic search was conducted in PubMed, Google Scholar, and the Cochrane Library for articles published from 2015 onward. Eligible studies included original in vitro and in vivo models, as well as observational studies, evaluating hazelnut or hazelnut-derived products in relation to CRC-related biological, metabolic, or clinical outcomes. Data extraction focused on bioactive composition, experimental models, molecular pathways, and fecal/metabolic markers of carcinogenesis. Results: A total of 11 studies were included after screening 24 records: 8 in vitro investigations, 2 in vivo animal experiments, and 1 epidemiological study. In vitro studies showed that hazelnut derivatives—including fermented hazelnuts and oil-based extracts—exert antiproliferative effects via BAX/BCL-2 modulation, increased caspase-3 activity, and oxidative stress reduction. In vivo studies confirmed improved lipid metabolism, modulation of bile acid composition (notably reduced lithocholic/deoxycholic acid ratio), and enhanced antioxidant defenses. FIBEROX®, a hazelnut skin extract enriched in dietary fiber, demonstrated promising effects on gut microbiota and bile acid detoxification. Conclusions: Hazelnut and their bioactive compounds may aid CRC prevention through multiple molecular and metabolic pathways. Further human studies are needed to confirm these effects and support dietary recommendations.